Conservation of marine biodiversity on a very large deep continental margin: how representative is a very large offshore reserve network for deep‐water octocorals?. Issue 1 (28th October 2016) - Althaus, Franziska; Williams, Alan; Alderslade, Philip; Schlacher, Thomas A.
Abstract: Aim: To evaluate the conservation performance of Australia's continental‐scale network of marine reserves for deep‐water octocorals using three criteria: (1) Representation : what fraction of the sampled deep‐water octocoral fauna within Australia's marine jurisdiction is contained in reserves?; (2) Species turnover : to what degree do reserves share species with non‐protected areas?; and (3) Biodiversity : do existing reserves spatially maximize protection of species richness? Location: Australia's continental exclusive economic zone and Norfolk Island region. Methods: A new Australia‐wide, taxonomically consistent, dataset for distributions of deep‐water octocorals (> 80 m depth) is used to calculate metrics of reserve performance for Australia's national marine reserve network. Results: Australia's reserve network represents 52% (270 of 518 species) of deep‐water octocoral species. Coral representation is roughly proportional to spatial extent of reserves in different regions. The proportion of species with joint distributions in reserves and non‐reserves ranges between 0% and 27% of the regional species pool; this may be a reflection of the high species turnover between sampling sites, and to some extent may also reflect sparse sampling coverage. Sites inside reserves have comparable species richness, contain similar numbers of rare species and do not differ in taxonomic diversity to sites outside reserves. Main conclusions: Australia's marine reserve network is a significant investment in conservation. The first broad biological evaluation of the network's performance, using deep‐water octocorals, indicates that whilst the level of species representation is broadly proportional to the network's spatial coverage, reserves do not appear to be areas of significantly higher octocoral biodiversity compared to areas outside reserves and that there is low species representation within highly protected (IUCN I or II) zones. Considering constraints on reserve expansion and spatial re‐configuration, 'off‐reserve' management tools (e.g. fishery closures, environmentally responsible practices by extractive industries) are likely to be important to enhance overall conservation outcomes.